The Influence of the Era of Globalization on Islamic Education at the Empathy Kita Ciampea Al-Qur'an Education Park, Bogor Regency - Syahidul Ihya; Anis Zohriah; Anis Fauzi; Rijal Firdaos (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The influence of the era of globalization on current Islamic education has a strong impact as a driving force in the development of education in the modern era. and provides major changes in all aspects of life which include technology and information, the influence of western culture and changes in the paradigm of education. but not all the impacts of the era of globalization are felt by every Islamic education in Indonesia because the education system in Indonesia is still uneven when viewed from its geological aspects so that it needs further research. So this research aims to find out what are the effects of the Era of globalization on Islamic education, especially in children's education parks. This research uses qualitative case study research conducted at the Ciampea Children's Education Park, Bogor Regency. Data collection techniques through observation and interviews with several teachers and students. The findings show that the era of globalization has a positive and negative impact on the development of Islamic education.